Bandgap inhomogeneity of MoS2 monolayer on epitaxial graphene bilayer in van der Waals p-n junction. (December 2016) - Ben Aziza, Zeineb; Henck, Hugo; Di Felice, Daniela; Pierucci, Debora; Chaste, Julien; Naylor, Carl H.; Balan, Adrian; Dappe, Yannick J.; Johnson, A.T. Charlie; Ouerghi, Abdelkarim
Abstract: Atomically thin MoS2 /graphene vertical heterostructures are promising candidates for nanoelectronic and optoelectronic technologies. In this work, we studied the optical and electronic properties of n doped single layer MoS2 on p doped bilayer graphene vdW heterostructures. We demonstrate a non-uniform strain between two different orientation angles of MoS2 monolayer on top of epitaxial bilayer graphene. A significant downshift of the E 1 2g mode, a slight downshift of the A1g mode, and photoluminescence shift and quenching are observed between two MoS2 monolayers differently oriented with respect to graphene; This could be mostly attributed to the strain-induced transition from direct to indirect bandgap in monolayer MoS2 . Moreover, our theoretical calculations about differently-strained MoS2 monolayers are in a perfect accordance with the experimentally observed behavior of differently-oriented MoS2 flakes on epitaxial bilayer graphene. Hence, our results show that strain-induced bandgap engineering of single layered MoS2 is dependent on the orientation angle between stacked layers. These findings could be an interesting novel way to take advantage of the possibilities of MoS2 and deeply exploit the capabilities of MoS2 /graphene van der Waals heterostructures.